Perancangan Aplikasi Belanja Sebagai Media Promosi Identitas Manasuka - Lubis, Dian; Harissman; Yuliarni (Indonesian Journal Publisher, 2025)
This study aims to design a shopping application based on UI/UX for Manasuka Official Store as a brand identity promotion media and sales platform for branded thrift shoes. The design is motivated by the limitations of Manasuka’s previous promotional media, which only relied on Instagram, thus failing to provide an efficient and integrated shopping experience for customers. The research uses a qualitative descriptive method, with data collection techniques through observation, interviews with store owners and customers, and literature studies. The design results in a prototype of the Manasuka application that applies a modern UI/UX concept, using Dark Green, Butter Scoth, Charcoal Black, and Silk White color schemes, and sans serif typography (San Francisco) to create a visual appearance consistent with the Manasuka brand identity. The application features product catalogs, product details, search filters, favorites, and a simple checkout system to facilitate user transactions. This application design is expected to strengthen Manasuka’s professional identity, increase customer trust, and expand market reach through digital platforms.